PEMIKIRAN MUHAMMAD SYAHRUR TENTANG KEWARISAN KALÂLAH DAN RELEVANSINYA TERHADAP PEMBARUAN HUKUM ISLAM - Arham, Akbaru Wustho; Elfia, Elfia (UIN Imam Bonjol Padang, 2020)
This study aims to analyze Muhammad Syahrur's thoughts about the inheritance of kalâlah and compare with the opinion of the ulema's jumhur 'and their relevance to the renewal of Islamic law. This research is a normative legal research or library research using secondary data. The results of this study revealed that: first, Syahrur interpreted kalālah with someone who died but did not have children, both boys and girls and did not have grandchildren, male or female, and did not have a father or mother and grandfather or grandmother. Secondly, in the case of the application of the distribution of the inheritance of kalâlah obtained by the heirs, Syahrur distinguishes the method of the distribution of kalālah assets in two conditions, namely the first and the second kalālah conditions. Third, Syahrur's thoughts on the inheritance of kalálah cannot be categorized as renewal in Islamic law because there is already a thought that is almost simultaneously with the pre- existing scholars namely Hazairin, one of Indonesian Islamic jurists who adheres to the concept of bilateral inheritance, especially regarding the inheritance of kalálah. Keywords: Muhammad Syahrur, kalâlah inheritance, renewal of Islamic law.